Sunlight photoactivity of rice husks-derived biogenic silica - de Cordoba, María C. Fernández; Matos, Juan; Montaña, Ricmary; Poon, Po S.; Lanfredi, Silvania [UNESP]; Praxedes, Fabiano R. [UNESP]; Hernández-Garrido, Juan C.; Calvino, José J.; Rodríguez-Aguado, Elena; Rodríguez-Castellón, Enrique; Ania, Conchi O. (Elsevier, 2019)
Carbon-containing SiO 2 -based photocatalysts were prepared by the solvothermal treatment of rice husk as biogenic precursor in the presence and absence of TiO 2 and used for the photocatalytic degradation of rhodamine-B under simulated solar light. Data showed that the prepared catalysts are mainly composed of biogenic silica and displayed mesoporous character with surface areas ranging from 65 to 174 m 2 g -1 . The obtained materials showed photocatalytic activity comparable to that of commercial TiO 2 -P25 powders for the degradation of rhodamine-B under sunlight. The calcination at 350 °C improved the photocatalytic activity of the biogenic precursor by three times in the absence of TiO 2 . At converse, calcination of sample SiO 2 -TiO 2 decreased the photoactivity due to the appearance of non-photoactive TiSiO 4 crystalline phases in the catalyst, as inferred by XRD and XPS. A reaction mechanism for rhodamine-B degradation excluding the deethylation pathway has been proposed, based on the evolution of the absorbance spectra of rhodamine-B upon the photocatalytic tests.
Keywords: Artificial solar light; Biogenic silica; Photocatalysis; Rhodamine B; Rice husks